Distinguishing dung from blue, red and yellow-backed duikers through noninvasive genetic techniques - Vliet, N. van; Zundel, S; Miguel, C.; Taberlet, P; Nasi, Robert (Wiley, 2008)
Dung counts have been widely used to estimate duiker abundance and densities in tropical African forests. However, one of the major limitations of this method is that species’ identification of dung based on morphological characteristics is extremely difficult in most cases. Some authors made the assumption that dung pellets could at least be distinguishable between the blue duiker, the red duikers and the yellow-backed duiker. However, this study is the first attempt to test the reliability of field identification. In this study, we suggest a method based on a noninvasive genetic protocol to identify duiker species. The comparison of field and genetic identifications shows that only dung from Cephalophus silvicultor was identified in the field without error. The rate of error for red duikers and the blue duiker is high and any attempt to distinguish among those species will result in wrong estimations for each species. We recommend the use of DNA tests to ensure reliable species’ identification when duiker censuses based on dung counts are used. This methodological input will probably strengthen the dung count technique and increase its reliability for duiker species abundance estimations and spatial distribution studies.